1988
DOI: 10.1093/ajcn/48.2.330
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid intake and urinary zinc excretion in newborn infants receiving total parenteral nutrition

Abstract: Zinc deficiency is well described in infants on total parenteral nutrition (TPN). Urinary Zn excretion is the major source of Zn loss in the parenterally fed infant; factors causing increased zincuria will predispose the infant to Zn deficiency and affect the recommended Zn intake dosage. Histidine, threonine, and lysine have been shown to bind Zn increasing its renal ultrafilterability. The effect of the infusion of high and low lysine (206 +/- 34 vs 158 +/- 38 mg.kg-1.d-1; means +/- SD), threonine (147 +/- 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The lack of cysteine may also decrease the infants' ability to store trace metals. Although toxicity to metals has not been observed in newborns receiving total parenteral nutrition, increased urinary trace metal excretion, as we have previosuly described, may indicate limited hepatic storage capacity (29). Neither the newborns nor the older infants in the current study received parenteral nutrients, thus we were unable to determine if the parenteral infusion of trace metals influenced metallothionein concentrations.…”
Section: Discussionmentioning
confidence: 60%
“…The lack of cysteine may also decrease the infants' ability to store trace metals. Although toxicity to metals has not been observed in newborns receiving total parenteral nutrition, increased urinary trace metal excretion, as we have previosuly described, may indicate limited hepatic storage capacity (29). Neither the newborns nor the older infants in the current study received parenteral nutrients, thus we were unable to determine if the parenteral infusion of trace metals influenced metallothionein concentrations.…”
Section: Discussionmentioning
confidence: 60%
“…For manganese the highest concentration was 47.72 mg kg -1 and was recorded in genotype ITOOK-1060. This value was much higher than the values reported by Ano and Ubonchi (2008) (Zlotkin and Buchanan, 1988). It was also reported that zinc dependent enzymes are involved in macronutrient metabolism and cell replication (Arinola, 2008).…”
Section: Analysis Of Variance For Nutritional Valuesmentioning
confidence: 51%
“…Cystine and histidine have the highest affinity to zinc among the other amino acids. Glutamine, lysine, and tyrosine also can bind zinc, but to a lesser degree [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperzincuria is also seen in sickle cell anemia, cirrhosis, diabetes mellitus, severe trauma, and in patients under total parenteral nutrition (TPN) [3][4][5][6]. In some of these conditions, hyperzincuria is accompanied by aminoaciduria.…”
Section: Introductionmentioning
confidence: 99%